2017
DOI: 10.1016/j.dcn.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia risk gene relates to representation of sound in the auditory brainstem

Abstract: Dyslexia is a reading disorder with strong associations with KIAA0319 and DCDC2. Both genes play a functional role in spike time precision of neurons. Strikingly, poor readers show an imprecise encoding of fast transients of speech in the auditory brainstem. Whether dyslexia risk genes are related to the quality of sound encoding in the auditory brainstem remains to be investigated. Here, we quantified the response consistency of speech-evoked brainstem responses to the acoustically presented syllable [da] in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 80 publications
4
39
1
2
Order By: Relevance
“…An increasing number of studies have investigated the function of RD risk genes in animal models [213], and the neurobiological and behavioral consequences of RD risk variants in humans [1431], motivating the need for a synthesis of these findings, especially as they relate to emerging avenues of human research on the role of neurochemistry [32] and neural oscillations [3336] in RD. We present a timely integration of diverse lines of current research linking some of the key neural and behavioral deficits associated with RD to basic neural processes.…”
Section: Premise Of the Neural Noise Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have investigated the function of RD risk genes in animal models [213], and the neurobiological and behavioral consequences of RD risk variants in humans [1431], motivating the need for a synthesis of these findings, especially as they relate to emerging avenues of human research on the role of neurochemistry [32] and neural oscillations [3336] in RD. We present a timely integration of diverse lines of current research linking some of the key neural and behavioral deficits associated with RD to basic neural processes.…”
Section: Premise Of the Neural Noise Hypothesismentioning
confidence: 99%
“…An important test for our hypothesis is whether similar loss of response consistency is present in humans carrying RD risk alleles. In the only study [31] to examine association between RD risk genes and the consistency of human neural responses to auditory stimuli, KIAA0391 risk alleles were associated with less consistent auditory brainstem responses (ABRs) in preliterate children. In the same study, DCDC2 risk alleles were associated with a trend towards more stable ABRs.…”
Section: Testing the Neural Noise Hypothesismentioning
confidence: 99%
“…An important test for our hypothesis is whether similar loss of response consistency is present in humans carrying RD risk alleles. In the only study [31] to examine the association between RD risk genes and the consistency of human neural responses to auditory stimuli, KIAA0391 risk alleles were associated with less-consistent auditory brainstem responses (ABRs) in preliterate children. In the same study, DCDC2 risk alleles were associated with a trend towards more stable ABRs.…”
Section: Rd Risk Alleles Will Be Associated With Impaired Cortical Aumentioning
confidence: 99%
“…An increasing number of studies have investigated the function of RD risk genes in animal models [2][3][4][5][6][7][8][9][10][11][12][13], and the neurobiological and behavioral consequences of genetic RD risk variants in humans [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], motivating the need for a synthesis of these findings, especially because they relate to emerging avenues of human research on the role of neurochemistry [32] and neural oscillations [33][34][35][36] in RD. Here, we present a timely integration of diverse lines of current research linking some of the key neural and behavioral deficits associated with RD to basic neural processes.…”
Section: Premise Of the Neural Noise Hypothesismentioning
confidence: 99%
“…A recent study found evidence that dyslexia-associated genes are related to the encoding of sounds in the auditory brainstem [18].However, there are musicians with dyslexia which scored better on auditory perception tests than the general population [17]. At the same time, these participants score worse on tests of auditory working memory, i.e., the ability to keep a sound in mind for seconds.…”
Section: Sound Perception and Dyslexiamentioning
confidence: 88%